"How video games changed my life": Life-Changing Testimonies and The Last of Us - Rautalahti, Heidi (Gamevironments, 2019)
In the following article, I explore YouTube videos and forum discussions on Reddit with content related to the theme or titled How video games changed my life , focusing especially on the mainstream video game The Last of Us (Naughty Dog 2013/2014). My aim is to understand how players use and follow an emerging and shared narrative describing a positive life-change. Through communal sharing online, the narratives afford a testimonial format or model. I see that the life-change narratives - or, in other words, transformational speeches - serve both as individual identity reflections, affirmations, and testimonies. Furthermore, through the act of public sharing on video platforms or through forum discussion, they can bring together an emerging community. Following Tuija Hovi s (2007, 2016) conceptualisations of religious narrative, the article shows how the argued testimonial tone underlines a unified and newly formed The Last of Us fan community. In addition, it presents a case study of how meaningful connections are built through shared narratives in today s online spaces. The article joins the scholarly conversations examining active meaning-making in popular culture.